TOTAL QUALITY MANAGEMENT (TQM) FRAMEWORK FOR THE COLLEGE OF HEALTH SCIENCES, MARIANO MARCOS STATE UNIVERSITY - Nagtalon, Federico V. (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
This study determined the extent of practice of CHS stakeholders on TQM principles as perceived by them with the end view of evolving a content validated total quality management framework for the College of Health Sciences, Mariano Marcos State University (MMSU). The study employed the research and development (R & D) model that involved the following phases: planning, development, and validation. The study found out that students, parents, alumni, faculty, administrators and non-teaching staff often practice the TQM principles along management leadership and commitment; continuous improvement; total customer satisfaction; faculty and non-teaching staff involvement; training and education; and rewards and recognition. However, some TQM principles are not always practiced especially on rewards and recognition. Hence there is a need for a TQM framework for the College to sustain its excellent performance.